Selective oxidation of methane over Fe-Zeolites by In situ generated H2O2 - Kang, Jongkyu; Park, Eun Duck (Catalysts, 2020)
Liquid-phase selective oxidation of methane into methane oxygenates, including methanol and formic acid, with molecular oxygen was investigated using Fe-zeolites and Pd/activated carbon in the presence of molecular hydrogen as a reducing agent. Various Fe-zeolites such as Fe-ZSM-5, Fe-mordenite, Fe-β, Fe-Y, and Fe-ferrierite were prepared by ion-exchange and compared for this reaction. Among them, Fe-ZSM-5 was selected for further study because this catalyst showed high activity in the selective oxidation of methane with relatively less leaching. Further, the effect of reaction temperature, pH, and the amount of catalyst was examined, and detailed investigations revealed that the leached Fe species, which were facilitated in the presence of acid, were mainly responsible for methane oxidation under the given reaction conditions.
Keywords: Formic acid; Hydrogen peroxide; Liquid-phase oxidation; Methane oxygenates; Partial oxidation of methane